The effect of the exercises brain on boxers’ eye-hand coordination, dynamic balance and visual attention performance - O. Çetin; M. Beyleroğlu; Y.E. Bağış; G. Suna (Physical Education of Students, 2018)
Purpose:  The purpose of this study is to investigate whether exercising brain performed by boxers have any kind of effect on visual attention, eye-hand coordination and dynamic balance performances of athletes.